Primary diffuse large B-cell lymphoma of the cranial vault with Trousseau syndrome: a case report - Tatsuya Uchida; Kenichi Amagasaki; Atsushi Hosono; Hiroshi Nakaguchi (Journal of Medical Case Reports, 2021)
Abstract Background It is extremely rare for primary non-Hodgkin’s lymphomas to occur singly in the cranial vault. One case diagnosed as primary diffuse large B-cell lymphoma is reported, initially misdiagnosed as metastatic skull tumor, complicated with Trousseau syndrome. Case description The patient was a 60-year-old Japanese woman with no particular previous medical history. In a head computed tomography examination for vertigo, bone destructive skull tumor covering the right frontal, parietal, and temporal bones was incidentally discovered. As positron emission tomography indicated an abnormal accumulation in the large intestine and multiple cerebral infarctions suspicious of Trousseau syndrome were observed on magnetic resonance images, a metastatic skull tumor due to colorectal cancer was first considered. However, various tumor markers were negative, and colonoscopic biopsy indicated no colorectal abnormality. After pathological examination of the resected tumor, it was diagnosed as diffuse large B-cell lymphoma. The tumor affected muscles and skin but did not develop in the brain or the dura mater. As further general examination revealed no other abnormalities, we considered that it was primary diffuse large B-cell lymphoma in the cranial vault associated with Trousseau syndrome. Treatment with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone and high-dose methotrexate reduced the residual lesion; coagulation abnormalities, which are frequently associated with Trousseau syndrome, also improved. Conclusions Skull tumors can result from a variety of malignancies, and their diagnosis may be complicated with Trousseau syndrome. However, even in cases of a single lesion in the cranial vault without invasion of the central nervous system, diffuse large B-cell lymphoma should be considered as a differential diagnosis.